1995
DOI: 10.1007/bf00188987
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal host defenses are less impaired by laparoscopy than by open operation

Abstract: There is a growing body of evidence that laparoscopic surgery is physiologically less injurious than open surgery. We hypothesized that the open technique results in a greater impairment of peritoneal and systemic defense mechanisms than does the laparoscopic technique. Nissen fundoplication, standardized in technique and duration, was performed in 16 pigs. The procedure was performed through a standard midline incision (OPEN, n = 8) or with laparoscopic technique and CO2 pneumoperitoneum (LAP, n = 8). The per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 14 publications
2
67
0
1
Order By: Relevance
“…However, changes in plasma endotoxin levels immediately after the operative procedure were not measured in those studies. Collet et al [24] reported peritoneal bacterial clearance to be greater in animals undergoing laparoscopic procedures than in those undergoing open procedures. Our data support this observation, and we believe that the transient increase in the endotoxin level may be mediated by increased translymphatic absorption due to the increased intra-abdominal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in plasma endotoxin levels immediately after the operative procedure were not measured in those studies. Collet et al [24] reported peritoneal bacterial clearance to be greater in animals undergoing laparoscopic procedures than in those undergoing open procedures. Our data support this observation, and we believe that the transient increase in the endotoxin level may be mediated by increased translymphatic absorption due to the increased intra-abdominal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In a controlled trial on children who underwent open or laparoscopic Nissen fundoplication, McHoney et al 32 reported no significant response in TNF-␣ levels in the postoperative period in either group. However, in an experimental study on pigs, Collet et al 33 showed increased serum TNF-␣ activity in open fundoplication compared with the laparoscopic group.…”
Section: Commentmentioning
confidence: 96%
“…With regard to the wounds induced by the surgical approach, clinical studies underlined improved healing and a reduction in wound complications due to the use of minimally invasive surgery [1,2]. Furthermore, animal studies have shown improved healing of skin infections and a less-impaired peritoneal host defence after CO 2 laparoscopy than after laparotomy [3,4]. In contrast, another experimental analysis of the effect of CO 2 insufflation on the quality of dermal wound healing revealed no difference when compared with laparotomy [5].…”
Section: Introductionmentioning
confidence: 99%